Evaluating the effects of an electric barrier on fish entrainment in an irrigation canal in Colorado. (5th January 2022) - Kowalski, Dan A.; Gardunio, Eric I.; Garvey, Chase A.
Abstract: Entrainment of fish in irrigation canals is a source of mortality for sport and native fishes and can affect populations and species diversity. To reduce entrainment of wild trout, an electric barrier was installed on the South Canal, an irrigation ditch on the Gunnison River in western Colorado, USA. The objective of this study was to evaluate the effectiveness of the barrier by marking fish upstream of it and estimating fish populations in the canal downstream before and after the barrier was operational. Three groups of fish were tagged and released upstream of the barrier: fish from the canal, wild fish from the Gunnison River, and hatchery‐reared Rainbow Trout. Boat electrofishing was completed in the canal reach below the barrier, and population estimates were made with the Huggins Closed Capture Model. The estimated Brown Trout population of the canal declined following the installation of the barrier, but Rainbow Trout remained stable because of the entrainment of small fish and their growth and survival in the canal. A total of 288 tagged fish less than 300 mm and 4 fish greater than 300 mm were recovered below the barrier, representing 1.3% of all tagged fish. The electric barrier appears to successfully exclude a portion of adult‐sized trout from the irrigation canal, but smaller adult and sub‐adult trout can pass the barrier. The entrainment, growth, and survival of smaller fish maintain a reduced but stable population of fish in the canal, but fewer entrained mature fish is likely a benefit to the populations of the Gunnison River.